Late Diagnosis of Complete Colonic and Rectal Duplication in a Girl with an Anorectal Malformation - Amr AbdelHamid AbouZeid; Shaimaa Abdelsattar Mohammad; Sherif Elhussiny Ibrahim; Anas Fagelnor; Ahmad Zaki (European Journal of Pediatric Surgery Reports, 2019)
Complete colonic duplication is rare, and usually occurs as a part of the caudal duplication syndrome. In such cases, the diagnosis is clinically evident by the presence of two ani arranged side by side in the perineum, which is commonly associated with duplication of the external genitalia as well (double phallus or double vestibule). In this report, we present a special case of anorectal anomaly that was associated with complete tubular colonic duplication. The diagnosis was initially missed due to the uncommon sagittal arrangement of duplicated rectum: one rectum was ending externally into the perineum by rectoperineal fistula, while the other was hidden by its internal termination into the vagina. Our final diagnosis for this case was a variant of anorectal anomaly in the female, which was associated with complete colonic duplication. One colon (which was in the free mesenteric border) terminated anteriorly into the vagina as a part of a “short common channel” cloaca, while the other colon terminated by rectoperineal fistula. Although the anomaly seems to be rather complex and confusing, yet our case was associated with an excellent outcome due to the benign type of anorectal anomalies (rectoperineal fistula and “short common channel” cloaca) and absence of significant sacral dysplasia; in addition to adequate identification of the abnormal anatomy by appropriate investigations and the staged approach for surgical reconstruction.